HCI in Business, Government and Organizations: eCommerce and Consumer Behavior: 6th International Conference, HCIBGO 2019, Orlando, FL, July 26-31: Proceedings, Part I - NAH, Fiona Fui-hoon (Institutional Knowledge at Singapore Management University, 2019)
This two-volume set LNCS 11588 and 11589 constitutes the refereed proceedings of the 6th International Conference on Business, Government, and Organizations, HCIBGO 2019, held in July 2019 as part of HCI International 2019 in Orlando, FL, USA. HCII 2019 received a total of 5029 submissions, of which 1275 papers and 209 posters were accepted for publication after a careful reviewing process. The 63 papers presented in these two volumes are organized in topical sections named: Electronic, Mobile and Ubiquitous Commerce, eBanking and Digital Money, Consumer Behaviour, Business Information Systems, Dashboards and Visualization, Social Media and Big Data Analytics in B.